Anakkon Hi Do Hamoraon Di Au: Fresh Graduate Career Planning for the Batak Toba Tribe - Tobing, David Frands Agus Elymar Lumban; Wibowo, Doddy Hendro (Budapest International Research and Critics University, 2022)
Career planning for fresh graduates in addition to finding and acquiring a job can also be useful to find a job that suits their interests or fields. This study aims to find out the picture of career planning in fresh graduates have tribes Batak Toba during the pandemic. This research is a qualitative research method using descriptive phenomenological. Selection of subjects using purposive sampling techniques. Respondents to the study were two men and one woman. Data collection in this study by conducting interviews. The results of this study showed that respondents had a picture of career planning, but during the pandemic, respondents experienced a challenge and obstacles, namely, the difficulty of finding a job, the number of competitors, and family and cultural factors that became obstacles. Culturally philosophy is being taught